The Concept of Ihsan in Al-Munir's Tafsir and Its Implications in the Workplace - Luthfiah, Isnaini; Astuti, Indri; Faridah, Faridah (STIT Sunan Giri Bima, 2025)
The value of ihsan is a concept of spiritual ethics in Islam that reflects the peak of religious perfection. This study aims to examine the concept of ihsan in Tafsir al-Munīr by Wahbah az-Zuhaili and analyze its implications in the contemporary world of work. This research uses a qualitative approach with the method of library research and thematic analysis (mauḍū'ī) of six main verses containing the word ihsan in the Qur'an. The results of the study show that ihsan in Tafsir al-Munīr not only covers the dimension of individual worship, but also social and professional values, such as sincerity, responsibility, communication ethics, social contribution, and the balance between worldly life and the hereafter. In the context of work, ihsan encourages the formation of an Islamic work ethic that is professional, productive, and worthy of worship. This concept is relevant as a solution to the moral crisis in the modern world of work that tends to be materialistic. This research enriches the treasures of thematic interpretation and offers an integration of Islamic spiritual values in professional practice.